ZYOFIELD: Alat pasteurisasi fermentasi berbasis teknologi pulsed electric field sistem fuzzy logic dalam pengolahan yoghurt - Kamsiatun Eka Pratama; Sindi Alfianti; Reza Rienaldy Putra; Gigih Widyawantoro; Daning Nurhalisa Kairupan; Joko Prasetyo (Jurnal Dedikasi Masyarakat, 2020)
Yogurt is a fresh and healthful fermented milk drink. This drink is made by a pasteurization process to eliminate pathogen bacteria in milk. The process was followed by a fermentation process with the help of Streptococcus thermophilus and Lactobacillus bulgaricus bacteria. The conventional pasteurization and fermentation process take a relatively long time, where the pasteurization process takes 15 minutes and the fermentation process takes 48 hours. In addition to the long process, the thermal pasteurization process can decrease the taste, color, and nutritional content of milk. The purpose of this research is to create a tool that can speed up the manufacture of yogurt without reducing the nutritional content of milk. ZYOFIELD is a tool that combines a Pulsed electric field (PEF) with an automatic fermentation system. PEF becomes a new method of milk pasteurization without the addition of heat, where the process temperature is 25o C so it may not reduce the important content in milk. This method utilizes an electric shock with a voltage of 20-80 kV to inactivate the pathogen bacteria within a short time of 5 minutes. ZYOFIELD is integrated with a controlled fermentation system where the fermentation temperature is maintained at 40-45° C, where at this temperature the fermentation process becomes optimum for 6 hours. The temperature on the fermentor is controlled by a fuzzy logic intelligent control system to regulate the temperature of the fermentation.